How to treat a fulminant erysipelas and sepsis caused by Myroides odoratimimus: case report and literature review. Issue 5 (3rd September 2017) - Willems, Philippe; Muller, Jan; Verhaegen, Jan; Saegeman, Veroniek; Desmet, Stefanie
Abstract : We report a case of a 77-year old male who developed a fulminant erysipelas and sepsis, caused by Myroides odoratimimus . Selecting the optimal antibiotic therapy for the treatment of infections with M. odoratimimus is challenging due to limited clinical experience with this micro-organism and its reported multidrug-resistance. Review of previous studies concerning in vitro antibacterial susceptibility and clinical experience with M. odoratimimus resulted in six case reports describing bacteremia, soft tissue and bone infections, pneumonia and urinary tract infections. In vitro susceptibility to aminoglycosides, fluoroquinolones and trimethoprim/sulfamethoxazole is variable. Treatment of M. odoratimimus infections should be based on antimicrobial susceptibility testing results. In a majority of the case reports, including the present one, treatment with fluoroquinolones proved to be a good therapeutic option.